Elastyczne kariery młodych Lubuszan - strategie radzenia sobie na współczesnym rynku pracy = Flexible careers of young inhabitants of Lubuskie Region - strategies for coping on the contemporary labour market - Róg-Ilnicka, Joanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to introduce the results of qualitative research on "Social and individual consequences of non-standard forms of employment" with particular emphasis on young inhabitants of Lubuskie Region, who often start their professional career path as non-standard employees. A depth interview was the technique used in the research and the interviewers had prepared instructions for the interview.
Keywords: labour market; flexible forms of employment; professional career; depth interview; rynek pracy; elastyczne formy zatrudnienia; kariera zawodowa; rozmowa kwalifikacyjna